Digital Fatigue And Clinical Decision-Making Among Nurses Using EHR Systems (The Review of Diabetic Studies, 2024)
Background: Electronic health record (EHR) use can lead to digital fatigue—cognitive, emotional, and physical exhaustion—that may impair nurses’ clinical decision-making.Objective: To examine the prevalence of digital fatigue among nurses and its impact on clinical decision-making.Methods: A cross-sectional study of 400 nurses from various clinical units was conducted using the Digital Fatigue Scale and Clinical Decision-Making Scale. Descriptive statistics, Pearson correlation, and multiple regression analyses assessed relationships between fatigue and decision-making, controlling for demographic and professional factors.Results: Between 85%–95% of nurses reported high levels of digital fatigue, with cognitive fatigue most pronounced. Clinical decision-making was moderately effective but negatively associated with fatigue (r = −0.52, p < .001). Regression analysis confirmed digital fatigue as a significant negative predictor of decision-making (β = −0.46, p < .001).Conclusion: Digital fatigue is widespread and substantially undermines nurses’ clinical decision-making. Workflow optimization, training, ergonomic interventions, and system usability improvements are needed to support nurses and maintain care quality.